THROUGH HAZEL'S EYES: DISABILITY, IDENTITY AND AGENCY IN THE FAULT IN OUR STARS - Gretty Andriana Sembiring; Inti Englishtina (Universitas 17 Agustus 1945 Semarang, 2025)
This article explores the representation of disability, identity, and personal agency through the character Hazel Grace Lancaster in the film The Fault in Our Stars (2014). Using the frameworks of Disability Studies, Narrative Prosthesis, and Jungian analytical psychology, the study analyzes how Hazel constructs her identity beyond her illness and how the film challenges traditional portrayals of disability. The findings reveal that Hazel negotiates her self-definition within both the medical and social models of disability, shifting from dependence to self-determination. Through her choices, relationships, and humor, she reclaims agency and resists being confined by her illness. This study concludes that The Fault in Our Stars redefines disability representation in young adult cinema, depicting disabled individuals as complex, autonomous, and emotionally capable.